IMPLEMENTING SEMANTIC MAPPING STRATEGY TO ENHANCE ELEVENTH GRADERS’ ORGANIZATION ASPECT OF THE WRITING SKILL - Afandi, Titah; Widiati, Utami; El Khoiri, Niamika (Universitas Negeri Malang, 2021)
Teaching English writing skill to Indonesian secondary students encounters many obstacles since English in Indonesia is a foreign language. Elaborating and organizing the ideas in pre-writing activity is one of the problems faced by students. The objective of this study was to examine how the implementation of semantic mapping strategy could enhance the eleventh graders’ writing skill, especially the organization aspect. Semantic mapping strategy was implemented in pre-writing activity since this strategy provides the visual concept of relations of the ideas. Classroom Action Research (CAR) was used as the research design in this study, and the implementation was carried out in three meetings for one cycle through the WhatsApp group. The research subjects were students of XI Science 4 class at SMA Negeri 4 Malang which consisted of 34 students. The results showed that this strategy succeeded in enhancing students’ writing scores in one cycle. The average score before the implementation was 69.9, and it became 86.8 after the implementation. Besides, the students’ organization aspect also increased significantly. In brief, this study offers a teaching strategy to overcome the problems in writing class by implementing semantic mapping strategy.